Three patients with both Hodgkin′s lymphoma and Castleman′s disease: Clinicopathologic correlations and lack of association with HHV-8 - Haque, Saadiya; Kirk Jr, Robert van (Indian Journal of Medical and Paediatric Oncology, 2009)
Background : The relationship between Hodgkin′s lymphoma (HL) and plasma cell-type Castleman′s disease (PCD) has been well documented. There have been over 20 cases reported in the literature and nearly all of them were either diagnosed concurrently, or were initially diagnosed as PCD and upon review were found to have interfollicular HL. Human herpes virus type 8 (HHV-8) is present in about 40% of cases with PCD. It predisposes patients to a much higher risk of other malignancies, including Kaposi′s sarcoma and non-Hodgkin′s lymphoma. Cases linked to HHV-8 are associated with a different morphology than cases that are not linked to HHV-8. It has been proposed that patients with both HL and CD will have lymph nodes with HHV-8-negative morphology.Materials and Methods : We present a series of three cases in a retrospective study where patients had both HL and PCD. Surgical pathology reports, clinical histories, and H and E and various immunohistochemical stains on initial work-up were examined and subsequent immunohistochemical stains for HHV-8 were obtained from the Methodist Hospital.Results:Patient 1 was diagnosed with PCD and interfollicular HL in the same lymph node. Patient 2 was first diagnosed with classic HL and 2 years later returned with enlarged lymph nodes clinically suspected to be recurrent HL. Histology showed angiofollicular hyperplasia and interfollicular plasmacytosis without Reed-Sternberg cells and a diagnosis of PCD was rendered. Patient 3, a male in his third decade, was diagnosed with nodular sclerosing HL in the thymus, and concurrently PCD in the mediastinal lymph nodes. All three cases had architectural features consistent with an HHV-8-negative morphology. Immunohistochemical stains for HHV-8 were done retrospectively and were negative.Conclusion:All three of our patients with both HL and CD had HHV-8-negative lymph node morphology and absence of HHV-8 by immunohistochemistry. These patients, therefore, are not at an increased risk for the development of subsequent malignancies, when compared to HHV-8-positive patients. Included in our series is one unique case where the diagnosis of HL preceded CD by 2 years.
Keywords: Castleman′s disease; Hodgkin′s lymphoma; HHV-8; plasma cell variant of Castleman′s disease